Dakwah Syarikat Islam Dan Kontribusinya Dalam Masyarakat Indonesia - Hariya Toni (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2020)
AbstractThis study aims to analyze the Islamic Syarikat da'wah movement and its contribution to Indonesian society. This research's object is the Islamic Syarikat organization and its research subjects regarding the contribution of the da'wah movement in three main fields, namely education, politics, and economics. This research uses a qualitative approach with literature study. Data collection was carried out using historical research techniques by collecting relevant primary sources. The results showed that, sociologically, this Islamic Syarikat played an important role or contributed from the New Order era to the present, making this organization a media of socialization for Muslims from several aspects: education, economics, and politics. The Islamic Syarikat Organization (SI) has an ideology to fight for and play an essential role in community empowerment in creating awareness and realizing Indonesian independence. It is manifested in the SI trilogy, namely, As clean as tawhid, as high as knowledge, and as smart as siasah. The impact of this research can encourage more active preaching activities, both for internal and external organizations.Keywords: Syarikat Islam; dakwah movement; contribution of dakwah.AbstrakPenelitian ini bertujuan untuk menganalisis gerakan dakwah Syarikat Islam dan kontribusinya bagi masyarakat Indonesia. Objek penelitian ini adalah organisasi Syarikat Islam dan subjek penelitiannya mengenai kontribusi gerakan dakwah dalam tiga bidang utama, yakni pendidikan, politik dan ekonomi. Penelitian ini menggunakan pendekatan kualitatif dengan studi pustaka. Pengumpulan data dilakukan dengan teknik historical research dan library research dengan mengumpulkan sumber-sumber primer yang relevan. Hasil penelitian menunjukkan bahwa secara sosiologis, Syarikat Islam ini sangat berperan penting atau berkontribusi dari zaman orde baru sampai dengan sekarang yang menjadikan organisasi ini sebagai media sosialisasi umat Islam dari beberapa aspek seperti bidang pendidikan, ekonomi dan politik. Organisasi Syarikat Islam (SI) memiliki ideologi untuk memperjuangkan dan memegang peranan penting dalam pemberdayaan masyarakat dalam menciptakan kesadaran rakyat serta mewujudkan kemerdekaan Indonesia. Hal ini terwujud dalam trilogi SI yakni, Sebersih-bersih Tauhid, Setinggi-tinggi ilmu dan Sepandai-pandai siasah. Adapun dampak penelitian ini dapat mendorong terhadap akitivitas dakwah lebih giat, baik untuk internal ataupun eksternal organisasi.Kata Kunci: Syarikat Islam; gerakan dakwah; kontribusi dakwah.